ASPP2 attenuates triglycerides to protect against hepatocyte injury by reducing autophagy in a cell and mouse model of non‐alcoholic fatty liver disease. Issue 1 (25th September 2014) - Xie, Fang; Jia, Lin; Lin, Minghua; Shi, Ying; Yin, Jiming; Liu, Yin; Chen, Dexi; Meng, Qinghua
Abstract ASPP2 is a pro‐apoptotic member of the p53 binding protein family. ASPP2 has been shown to inhibit autophagy, which maintains energy balance in nutritional deprivation. We attempted to identify the role of ASPP2 in the pathogenesis of non‐alcoholic fatty liver disease (NAFLD). In a NAFLD cell model, control treated and untreated HepG2 cells were pre‐incubated with GFP‐adenovirus (GFP‐ad) for 12 hrs and then treated with oleic acid (OA) for 24 hrs. In the experimental groups, the HepG2 cells were pre‐treated with ASPP2‐adenovirus (ASPP2‐ad) or ASPP2‐siRNA for 12 hrs and then treated with OA for 24 hrs. BALB/c mice fed a methionine‐ and choline‐deficient (MCD) diet were used to generate a mouse model of NAFLD. The mice with fatty livers in the control group were pre‐treated with injections of GFP‐ad for 10 days. In the experimental group, the mice that had been pre‐treated with ASPP2‐ad were fed an MCD diet for 10 days. ASPP2‐ad or GFP‐ad was administered once every 5 days. Liver tissue from fatty liver patients and healthy controls were used to analyse the role of ASPP2. Autophagy, apoptosis markers and lipid metabolism mediators, were assessed with confocal fluorescence microscopy, immunohistochemistry, western blot and biochemical assays. ASPP2 overexpression decreased the triglyceride content and inhibited autophagy and apoptosis in the HepG2 cells. ASPP2‐ad administration suppressed the MCD diet‐induced autophagy, steatosis and apoptosis and decreased the previously elevated alanine aminotransferase levels. In conclusion, ASPP2 may participate in the lipid metabolism of non‐alcoholic steatohepatitis and attenuate liver failure.